Perceived prevalence of COVID-19 and its association with personal protective equipment utilization among healthcare workers in Rivers State - Amadi, Christian Emeka; Alegbeleye, Justina Omoikhefe (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
The use of personal protective equipment (PPE) has been at the forefront of the combat against the COVID-19 pandemic. This study investigated the prevalence of COVID-19 and its association with personal protective equipment utilization among healthcare workers in Rivers State. The study was a descriptive cross-sectional survey of 2,696 healthcare workers in secondary and tertiary health facilities in Rivers State. A multi-stage sampling method was adopted, and data was collected using a structured questionnaire. Statistical analysis was done using the Statistical Package for Social Sciences (SPSS) version 25.0, and the level of statistical significance was set at a p-value of ≤ 0.05. Results are presented in mean and percentages. The study showed a high perceived prevalence of COVID-19 among healthcare workers in Rivers State. There was a significant association between adherence to PPE utilization and the perceived prevalence of COVID-19 among healthcare workers (p-value <0.05). Poor PPE utilization is associated with a high perceived prevalence of COVID-19 among healthcare workers in Rivers State. It was recommended that the management boards of health institutions should improve on the adherence to PPE utilization by setting up committees to enforce the use of PPE among healthcare workers in Rivers State.